Pengabdian IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI FILM NGERI-NGERI SEDAP KARYA BENE DION BAGI MASYARAKAT DESA TALANG JALI: IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI FILM NGERI-NGERI SEDAP KARYA BENE DION BAGI MASYARAKAT DESA TALANG JALI - muinah muinah; sigit gunanto (Sentra Kekayaan Intelektual dan Publikasi Ilmiah, 2023)
Character education is an activity to improve yourself and train yourself in a better direction. Character education in the family must be considered because the formation of a person's character first occurs and is trained through the family. As for character education within the scope of the family usually includes: religious attitude, honesty, discipline, hard work, independence, democracy, curiosity, friendship, and responsibility. The process of delivering this character education lesson is through the media of the film Ngeri-ngeri sedap by Bene Dion. This film depicts the life of a Batak family whose parents still adhere to the old culture, that is, they want their children to become civil servants. This activity was held as the highlight of the agenda of KKN Knowledge Transfer students at Muhammadiyah University Kotabumi in 2023. This activity was attended by the Talang Jali village community, the event went smoothly and went well.